Toward a publics-driven, emotion-based approach in crisis communication: Testing the Integrated Crisis Mapping (ICM) Model - JIN, Yan (Institutional Knowledge at Singapore Management University, 2006)
Extending current situation-based conceptualizations of crisis response, theauthors have developed a more universal and systemic approach to understandingthe role of emotions in crises. The authors’ Integrated Crisis Mapping (ICM)model is based on a public-based, emotion-driven perspective where differentcrises are mapped on two continua, the organization’s involvement with the crisisissue and primary public’s coping strategy. The initial test suggested theoreticalrigor in the model and found that publics involved in crises pertaining toreputational damage, technological breakdown, industrial matters, labor unrest,and regulation/legislation, are likely to feel anxious, angry, and sad. At the sametime, they are likely to engage in conative coping and take active steps to restoresome semblance of normalcy within their immediate environment. As counter-intuitive as this may appear, organizations embroiled in these crises need only toengage moderately, rather than intensely, in reaching out to the publics. Thisstudy is the first of a series of studies to generate what Yin (2003) termed“analytic generalization” (p. 33). The findings from this study, arguably, representthe imprints of an initial trail that may open up to a possibly new vista of researchin crisis communication.